(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The use of a developed algorithm for selecting surgical treatment tactics for esophageal hiatal hernias has reduced the incidence of postoperative complications and mortality.